An Empirical Study on Access and Use of Formal Money Transfer Mechanisms among Migrant Workers in Kerala - Dileep G Menon; Nandu Narayanan R and Sougata Ray
Since the formation of money, the ability to transfer it from one place to another or “Velocity of Money” had been the backbone of an economy. It has facilitated in the creation of wealth through job creation, trade practices and economic activities. With the advancement of mobile technologies and devices, individuals are now able to conduct banking services from anywhere at any time. For a large section of the population in India, such mobile access to money transactions can act as a way to achieve financial inclusion.The level of acceptance and use of the formal money transfer mechanisms in India is an important issue of research.The purpose of this research is to critically examine and validate the acceptance and use of technology-based mechanisms of money transactions among the migrant workers in Kerala. A primary survey was conducted using validated questionnaire requesting response for the factors obtained from literature review.The factors considered in the study are Age, State of origin, Education level, Monthly average income and Type of job. The data was collected from 200 migrant workers spread across four districts of Kerala. The findings imply that even though the migrant workers are aware and have access to various modes of money transfer, they stick on to the traditional banking processes for transferring their money. The study provides a thorough empirical insight on the acceptance of new technologies in financial transaction methods among migrant workers in Kerala